The Impact of Work Life Policies, Empowerment, Training and Development and Job Satisfaction on Employees Performance with Mediation Organizational Citizenship Behavior (OCB) - Arif Darmawan; Theresia Sinaga (Journal of Applied Accounting and Taxation, 2018)
Human resources is a company’s very valuable asset that should always be kept level of OCB to improve their performance. The purpose of this study to determine the impact of work life polices, empowerment, training and development, job satisfaction on employee performance with OCB as mediation variable in using 140 permanent lectures majoring in management and economics in Batam as respondents. The data analysis technique used is multiple regression analysis, path analysis and Sobel test to test the effect of intervening variable. This study found that OCB can indirectly affect the relationship between work life polices, empowerment, training and development, job satisfaction on employee performance. This result illustrate that the performance of employees will increase as improved OCB, so it is important for the company to pay more attention to the work life polices, empowerment, training and development, job satisfaction so that the employee’s satisfaction is always maintained.